Factors Affecting The Implementation Of SAK EMKM In Restaurant Business At Banyumas Regency - Dimas Arya Denta; Eko Suyono; Rini Widianingsih (Publikasi Indonesia, 2023)
This research is quantitative research in the restaurant business at Banyumas Regency. This research takes the title